LAW ENFORCEMENT AGAINST POLICE OFFICERS INVOLVED IN DRUG ABUSE BASED ON JUSTICE VALUES - Budiarsih, Budiarsih; Sushanty, Vera Rimbawani (YURIS: Journal of Court and Justice, 2024)
Drug abuse in Indonesia is a serious problem that not only involves the general public, but also law enforcement officials, including the police. This study aims to find out the punishment in deciding cases of criminal acts of narcotics abuse by members of the Police and what are the obstacles faced in the investigation process against members of the National Police who commit crimes of narcotics abuse. This research includes normative juridical research with descriptive research type. Sources of data in this study using library research, field as well as secondary data and primary data. Data analysis uses qualitative. Based on the results of the discussion, it can be concluded that the process of law enforcement against members of the police who are ensnared in cases of criminal acts of drug abuse is in accordance with the applicable laws and regulations, where in the enforcement process both are carried out at the police level (investigation and investigation stages), at the prosecutor's level (the prosecution stage) up to the judicial level (judge's decision), the whole is the same as if the general public committed the crime of narcotics abuse. The legal process against the police is in accordance with Article 29 Paragraph (1) of Law No. 2/2002 concerning the Indonesian National Police. The process of enforcing the police professional code of ethics for members of the police who are caught in criminal cases of narcotics abuse has not been carried out to the fullest extent possible where the police do not directly take firm action against members who are caught in criminal cases of narcotics abuse, as if the police are still protecting their members and it is considered that after their members have been tried in court general court and found guilty of committing a narcotic crime.